The emerging "Post-Doha" agenda and the new regionalism in the Asia-Pacific - Michael G. Plummer (Asian Development Bank Institute (ADBI), 2012)
This paper considers emerging commercial policy challenges facing the Asia-Pacific region in light of the impasse reached at the Eighth World Trade Organization (WTO) Ministerial Meeting in December 2011. It underscores that, while marginal liberalization of trade barriers under the Doha Development Agenda may not be forthcoming in the short- or even medium-term, the WTO has been successful in erecting a rules-based system of global governance and continues to be extremely important to the future health of the international trading system. Nevertheless, one can expect the current trend toward bilateral and regional free-trade areas (FTAs) will continue, particularly since it is easier to make progress toward "deep integration" in a smaller group of like-minded countries than in the context of the general WTO membership. This paper considers how the FTA trend is developing in the Asia-Pacific region and what its prospects are in the future. It stresses that regional - as opposed to bilateral - arrangements will be essential to the region for economic (e.g., supporting regional production networks) as well as diplomatic-political goals. This "new regionalism" which has been supported by Asia-Pacific Economic Cooperation (APEC), will lead to significant reductions in the costs associated with bilateral FTAs (e.g., lower costs associated with rules of origin, improved utilization rates) and has many advantages over "noodle-bowl" bilateralism.
Keywords: F13; F15; 330; world trade organization; doha development agenda; post-doha agenda; new regionalism; asia-pacific; free trade areas; Freihandelszone; WTO-Recht; Regionale Wirtschaftsintegration; Asiatisch-pazifischer Raum